2020
DOI: 10.1038/s41598-020-73172-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparing blood pressure measurements between a photoplethysmography-based and a standard cuff-based manometry device

Abstract: Repeated blood pressure (BP) measurements allow better control of hypertension. Current measurements rely on cuff-based devices. The aim of the present study was to compare BP measurements using a novel cuff-less photoplethysmography-based device to a standard sphygmomanometer device. Males and females were recruited from within the general population who arrived at a public BP screening station. One to two measurements were taken from each using a sphygmomanometer-based and the photoplethysmography-based devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 25 publications
0
56
0
2
Order By: Relevance
“…Thus far, studies investigating maternal hemodynamics during labor and delivery have yielded conflicting results, especially regarding magnitude and timing of hemodynamic adaptations. Previous studies suggested inconsistent results on the effect of EA on maternal hemodynamics during labor [19,[23][24][25][26]. EA induces a sympathetic blockade that causes vasodilatation and a decrease in venous return to the heart, which can result in maternal hypotension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, studies investigating maternal hemodynamics during labor and delivery have yielded conflicting results, especially regarding magnitude and timing of hemodynamic adaptations. Previous studies suggested inconsistent results on the effect of EA on maternal hemodynamics during labor [19,[23][24][25][26]. EA induces a sympathetic blockade that causes vasodilatation and a decrease in venous return to the heart, which can result in maternal hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, abrupt onset of pain relief may trigger a reduction in blood pressure. However, these effects are seen in only some of the studies and reported clinically in only 0-14% of laboring women receiving EA [23][24][25][26][27]. Recently, Ashwal et al [19] compared maternal hemodynamics following vaginal and cesarean deliveries determined by a whole body bioimpedance-based device.…”
Section: Discussionmentioning
confidence: 99%
“…A time-consuming approach was suggested in [52] for estimating SBP and DBP based on back-propagation error neural networks. Several techniques were implemented to reduce feature redundancy, optimize the BP estimation, and determine the initial weights and threshold of the network.…”
Section: Background and Related Workmentioning
confidence: 99%
“…To the best of our knowledge, this is the only cleared wearable wireless medical-grade device to provide all these measurements. The sensor tracks vital signs derived from changes in the pulse contour, following baseline calibration using an approved non-invasive, cuffbased device, and is based on Pulse Wave Transit Time (PWTT) technology, combined with Pulse Wave Analysis (PWA) (see, for example, 15,16 ). The sensor continuously collected data at 10minute intervals for the entire duration of the 96-hour experiment.…”
Section: The Chest-patch Sensormentioning
confidence: 99%